2016
DOI: 10.1016/j.stem.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

CD82/KAI1 Maintains the Dormancy of Long-Term Hematopoietic Stem Cells through Interaction with DARC-Expressing Macrophages

Abstract: Hematopoiesis is regulated by crosstalk between long-term repopulating hematopoietic stem cells (LT-HSCs) and supporting niche cells in the bone marrow (BM). Here, we examine the role of CD82/KAI1 in niche-mediated LT-HSC maintenance. We found that CD82/KAI1 is expressed predominantly on LT-HSCs and rarely on other hematopoietic stem-progenitor cells (HSPCs). In Cd82(-/-) mice, LT-HSCs were selectively lost as they exited from quiescence and differentiated. Mechanistically, CD82-based TGF-β1/Smad3 signaling le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
129
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 46 publications
2
129
1
Order By: Relevance
“…7 More recently, DARC-expressing MFs maintain the dormancy of long-term HSCs through interaction with CD82/KAI1. 8 However, whether MFs have the ability to directly regulate HSC self-renewal is unknown. Activated MFs exhibit plasticity and exert diverse functions along a spectrum between classical (M1) or alternative (M2) activation (or polarization).…”
Section: Introductionmentioning
confidence: 99%
“…7 More recently, DARC-expressing MFs maintain the dormancy of long-term HSCs through interaction with CD82/KAI1. 8 However, whether MFs have the ability to directly regulate HSC self-renewal is unknown. Activated MFs exhibit plasticity and exert diverse functions along a spectrum between classical (M1) or alternative (M2) activation (or polarization).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent findings suggest that HSC can be subdivided into LT or short-term (ST) HSC of which the latter have a greater propensity for lineagespecific differentiation (11 Hoxb5 to these markers for providing additional definition of the LT-HSC population (12). The study by Hur et al (13) identifies yet another marker for LT-HSC and furthermore ascribes a mechanistic role to this marker. Cd82/Kai1 codes for a membrane receptor (denoted CD82 onwards) belonging to the tetraspanin family of receptors, which interacts with the Darc/ Cd234 gene product (denoted Darc onwards) (14).…”
Section: December 2012mentioning
confidence: 99%
“…CD82 (KAI1) was initially identified as being involved in the T cell activation process. 2 A previous study identified DARC (CD234) expressed on ECs as the counterpart molecule to CD82 expressed on cancer cells. Interestingly, CD82-DARC interaction suppresses tumor metastasis.…”
mentioning
confidence: 99%
“…1). 2 At the onset of that study, our 2 main questions were: first, what is the exclusive surface marker of LT-HSCs that distinguishes them from short-term repopulating HSCs (ST-HSCs) or progenitors; and second, what is the main stem cell niche player that supports LT-HSC quiescence? Consistent with previous reports, CD82 was broadly expressed in various cell types in murine BM.…”
mentioning
confidence: 99%